PEMANFAATAN DAN PENDAMPINGAN PEMBUATAN QR CODE DAN FACEBOOK MARKETPLACE SEBAGAI MEDIA PROMOSI WISATA DI DESA APUAN SUSUT BANGLI - Gde Iwan Setiawan; Ni Luh Gede Ambaradewi; I Kadek Juniarta; I Nyoman Bagus Suweta Nugraha (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2023)
The purpose of this service activity is to develop the potential of tourist destinations in Apuan village by utilising information technology-based local wisdom, which empowers the potential of the community in increasing family income through increasing creative economic businesses supporting tourist destinations. While the specific target of this service activity, namely in the development of tourism destination promotion. This activity was carried out for 1 (one) month, with several stages of activities in the implementation of this Community Service (PKM), including: (1) initial evaluation; (2) group formation; (3) QR-Code making training; (4) Facebook Marketplace making training; (5) business management assistance; (6) final evaluation, and (7) special monitoring for sustainability. The activities have been implemented, and the village community has begun to utilise Facebook Marketplace as a medium for digital-based tourism promotion.